STRATEGI PENINGKATAN KINERJA PERUSAHAAN MELALUI PENGELOLAAN SUMBER DAYA MANUSIA DAN KEPUASAN KERJA DAN DAMPAKNYA TERHADAP PRODUKTIVITAS KARYAWAN - Iskandar, Dhany (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2018)
One of the key issues in a company's success in achieving its vision and mission is the quality of Human Resources (HR). The Objektive of this study is to determine the importance of human resource management strategies and job satisfaction that has an impact the productivity of employees. 1. In this research, we observed the appliedship Human Resources on management of PT Swadharma Sarana Informatika (SSI), PT. Sarana Reswara Abadi (SRA) and PT. Reswara Prima Express (Respex), Based on service target and its operation, 2. In this research, we prepare questionaire for our respondents which will be interviewed and the outcome will be used for the analysis on the achievement in company’s performance is probability the corporate productivity. 3. It can be identified what strategy does the company to achieve its vision and mission. 4. It can be concluded that the quality of human resources need to be improved the target on the company's performance from the point of the current performance.